An investigation of children's empathic dispositions and behaviours across seven countries. Issue 5 (16th June 2021) - Kozloff, Violet; Cowell, Jason M.; Huppert, Elizabeth; Gomez‐Sicard, Natalia; Lee, Kang; Mahasneh, Randa; Malcolm‐Smith, Susan; Selcuk, Bilge; Zhou, Xinyue; Decety, Jean
Abstract: This study examined individual influences on child empathy, the relationship between child and parent empathy, and the relationship between empathy and prosociality across seven countries. A large sample of children ( N  = 792, 49% female) from the ages of 6–10 years completed a situational empathy task, as well as a dictator game to assess prosociality. The questionnaire of cognitive and affective empathy was used to assess parents' and children's empathic dispositions. Children participated from Canada, China, Colombia, Jordan, South Africa, Turkey, and the United States. Situational empathy, empathic disposition, and prosociality were all positively associated with age. Boys displayed less situational empathy and lower empathic disposition than girls. Parental empathic disposition predicted the same dispositions in children but were not related to children's situational empathy or prosociality. No association was found between child prosociality and child empathic disposition. Overall, the results suggest similar ontologies of empathic disposition and situational empathy across countries.